ANALISIS PENGARUH DEBT TO EQUITY RATIO DAN NET PROFIT MARGIN TERHADAP RETURN ON ASSET PADA INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA - Anak Agung Putri Suardani; I Ketut Astawa (Valid: Jurnal Ilmiah, 2016)
The research is aiming to analyse the influence of debt to equity ratio, net profit margin to return on an asset in the manufacturing industry in Indonesia Stock Exchange by using purposive sampling. The result shows that partially debt to equity ratio has positive influence but no significant to return on asset, the net profit margin has a positive influence and significant to return on an asset in the manufacturing industry in Indonesia Stock Exchange. Simultaneously debt to equity ratio, net profit margin influence significantly to return on an asset in the manufacturing industry in Indonesia Stock Exchange